1988
DOI: 10.1007/bf00640669
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate accumulation in intermittent supramaximal exercise

Abstract: Blood lactate accumulation rate and oxygen consumption have been studied in six trained male runners, aged 20 to 30 years. Subjects ran on a treadmill at a rate representing 172 +/- 5% VO2max for four 45 s sessions, separated by 9 min rest periods. Oxygen consumption was measured throughout. Blood lactate was determined in samples taken from the ear and VO2 was measured at the end of each exercise session, and two, five and nine minutes later. After the fourth exercise session, the same measurements were made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

1990
1990
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Experiments in vitro using frog sartorious muscle have shown that extracellular pH and bicarbonate concentration can influence lactate and H + efflux from the muscle, and are also related to tension recovery (Mainwood and Worsley-Brown, 1975 Renaud 1989). Furthermore, Rieu et al (1988) also observed a decrease in 'delta' lactate values when blood lactate concentration was increased by repeated 45 s treadmill runs at 175% VO 2 max. Similar findings were reported by McCartney et al (1986) and Spriet et al (1989).…”
Section: Discussionmentioning
confidence: 84%
“…Experiments in vitro using frog sartorious muscle have shown that extracellular pH and bicarbonate concentration can influence lactate and H + efflux from the muscle, and are also related to tension recovery (Mainwood and Worsley-Brown, 1975 Renaud 1989). Furthermore, Rieu et al (1988) also observed a decrease in 'delta' lactate values when blood lactate concentration was increased by repeated 45 s treadmill runs at 175% VO 2 max. Similar findings were reported by McCartney et al (1986) and Spriet et al (1989).…”
Section: Discussionmentioning
confidence: 84%
“…It appears that the dissociation between the recovery oxygen consumption and the accumulation and fate of lactate, along with the influence of a number of factors that stimulate mitochondrial respiration after exercise, undermine its use. [19,20] This discredits the traditional concept of paying back a debt that was incurred during exercise by restoring anaerobic stores. Factors known to elevate oxygen consumption during recovery that are not directly related to anaerobic energy release during exercise include an elevation in temperature, increases in hormonal activity and the general elevated energy needs associated with a return to homeostasis.…”
Section: Methods Used To Evaluate Energy Releasementioning
confidence: 99%
“…The use of oxygen debt as a measure of the anaerobic capcity, however, has been discredited by several authors (6, 30, 40). Hermansen (6) suggested that the influence of several factors affecting the resting oxygen uptake was the cause of a lack of confidence in the method, but it appears that the dissociation between the recovery oxygen consumption and the accumulation and fate of lactate, along with the influence of a number of factors which stimulate mitochondrial respiration after exercise, undermine its potential use (57,69). It has been found that the preferential fate of lactate is as a substrate for oxidation and not glycogen resynthesis (57, 70) and it therefore does not represent extra oxygen consumption, as lactate merely replaces other substrates in oxidation.…”
Section: Oxygen Debtmentioning
confidence: 99%